Implementación de una base de datos heterogénea distribuida entre los SGBDs ORACLE, MySQL y PostgreSQL con replicación, mediante un script bash implementado en el sistema operativo CentOS usando software libre - Flores Castro, Edwin Geovanny (2018)
This article allows to obtain a heterogeneous distributed database with replication in a CentOS environment in less than 5 minutes, using a bash script, using only free software. The idea is focusedon having a slave that will be ORACLE and the master nodes will be in MySQL and PostgreSQL, in order to reduce costs when designing and implementing a distributed database since the power of a manager is maximized of payment, which is Oracle, with the free and good performance of MySQL and PostgreSQL. The result of this article will be an ODBC that configures the two managers without spending a single cent and in record time, and thus be able to obtain a distributed database made up of different managers, who work as one.